Making Decisions under Ambiguity: Judgment Bias Tasks for Assessing Emotional State in Animals - Roelofs, Sanne; Boleij, Hetty; Nordquist, Rebecca E.; van der Staay, Franz Josef (Frontiers in Behavioral Neuroscience, 2016)
Judgment bias tests are considered as a family of promising tools in the assessment of emotional states of animals. Judgment bias tasks (JBTs) provide a cognitive measure of optimism and/or pessimism by recording behavioral responses to ambiguous stimuli. For instance, a negative emotional state is expected to produce a negative or pessimistic judgment of an ambiguous stimulus, whereas a positive emotional state produces a positive or optimistic judgment of the same ambiguous stimulus. Measuring an animal’s emotional state or mood is relevant in both animal welfare research and biomedical research. This is reflected in the increasing use of JBTs in both research areas. We discuss the different implementations of JBTs with animals, with a focus on their potential as an accurate measure of emotional state. JBTs have been successfully applied to a very broad range of species, using many different types of testing equipment and experimental protocols. However, further validation of this test is deemed necessary. For example, the often extensive training period required for successful judgment bias testing remains a possible factor confounding results. Also, the issue of ambiguous stimuli losing their ambiguity with repeated testing requires additional attention. Possible improvements are suggested to further develop the JBTs in both animal welfare and biomedical research.